Pre- and Post-Cracking Resistance of Steel Fiber Reinforced Concrete Flexural Members with GFRP Bars - Mohammed, Shatha D.; Abbas, Rafaa M.; Salman, Hamza M.; Oukaili, Nazar K.; Allawi, Abbas A. (Civil Engineering Journal, 2025)
This research investigates the pre- and post-cracking resistance of steel fiber-reinforced concrete specimens with Glass Fiber Reinforced Polymer (GFRP) bars subjected to flexural loading. The purpose is to modify the ductility and cracking resistance of GFRP-reinforced beams, which are prone to early cracking and excessive deflections instigated by the low modulus of elasticity of GFRP. Six self-compacting concrete specimens (1500×240×200 mm), incorporating steel fibers of two lengths (25 mm and 40 mm) with varying distribution depths, were tested to assess their structural performance. The results indicate significant enhancements in cracking resistance, stiffness, energy absorption, ductility, and flexural strength. Tested beams reinforced with 40 mm-long steel fibers exhibited a 23.9%–24.2% development in the ultimate moment capacity associated with the steel-reinforced specimens, whereas those with 25 mm fibers showed smaller increases (2.7%–3.1%). The cracking resistance improved by up to 33.3% in beams with 40 mm-long fibers and by 16.67%–20% in those with 25 mm-long fibers, associated with a non-fibrous GFRP specimen. Additionally, the inclusion of 40 mm hooked-end steel fibers significantly enhanced ultimate deflection, with peak deflections increasing by 30.2%–44.8% compared to steel-reinforced beams. Fibrous GFRP-reinforced beams exhibited up to 154% higher energy absorption under ultimate load than a non-fibrous GFRP beam. All fibrous GFRP-reinforced beams achieved deformation-based ductility indices between 4.2 and 6.9, exceeding the minimum threshold of 4 for adequate deformability. These findings confirm that incorporating 40 mm steel fibers significantly improves the structural behavior of GFRP-reinforced concrete specimens, offering valuable insights for optimizing their design.